Sistem Pakar Diagnosa Penyakit Zika Dengan Menerapkan Metode Case Base Reasoning - Muhammad Syahrizal; Rika Irwanti; Muhammad Sayuthi (STMIK Budi Darma, 2018)
Zika's disease or zika fever is a zika virus, the zika virus is spread by infected Aedes mosquitoes, this mosquito becomes infected after bites the sufferer who has the virus. Zika's disease worse when exposed to pregnant women, because women infected with this virus will automatically pass it to the baby in the womb, and can cause death if the baby survives will experience the baby aka birth with a smaller head than it should be. To help the problems faced by experts or medical personnel in diagnosing Zika's disease in these patients, where the activity is seen from the symptoms suffered by the patient. By using Case-Based Reasoning Method is expected to assist medical personnel or experts in calculating the diagnosis of the patient and the expert can know whether the patient must have zika disease or vice versa.